2015
DOI: 10.1039/c5ta00986c
|View full text |Cite
|
Sign up to set email alerts
|

An InIII-based anionic metal–organic framework: sensitization of lanthanide (III) ions and selective absorption and separation of cationic dyes

Abstract: An In III -based anionic framework (In III -MOF) with 4-connected SrAl 2 topology was constructed. The In III -MOF with permanent porosity functions as a host for encapsulation of Ln 3+ ions through ion-exchange processes. The photophysical properties of as-prepared Ln 3+ @In III -MOF were investigated and the results showed that the In III -MOF could serve as an antenna to sensitize Ln 3+ cations, especially suitable for Tb 3+ and Eu 3+ ions. The possible sensitization mechanism has been studied by surface ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
55
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(56 citation statements)
references
References 62 publications
1
55
0
Order By: Relevance
“…To obtain MOF‐based sensors for the targeted application, their stability within base, acid, along with water is the principal problem to be considered. Recent literature have revealed that the In(III)‐based MOFs show good water stabilities due to the strong coordination bonds of donor O atoms and central In(III) ions . In this study, a novel water‐stable MOF based on In(III), namely [In 3 (btta) 2 (OH) 3 (H 2 O)]·(DMA) 2 ( 1 , DMA = N , N ‐dimethylacetamide), based on (2 E ,2′ E ,2″ E )‐3,3′,3″‐(benzene‐1,3,5‐triyl)triacrylic acid (H 3 btta), was obtained via a solvothermal reaction and structurally characterized by X‐ray diffraction of single crystal along with elemental analysis.…”
Section: Introductionmentioning
confidence: 97%
“…To obtain MOF‐based sensors for the targeted application, their stability within base, acid, along with water is the principal problem to be considered. Recent literature have revealed that the In(III)‐based MOFs show good water stabilities due to the strong coordination bonds of donor O atoms and central In(III) ions . In this study, a novel water‐stable MOF based on In(III), namely [In 3 (btta) 2 (OH) 3 (H 2 O)]·(DMA) 2 ( 1 , DMA = N , N ‐dimethylacetamide), based on (2 E ,2′ E ,2″ E )‐3,3′,3″‐(benzene‐1,3,5‐triyl)triacrylic acid (H 3 btta), was obtained via a solvothermal reaction and structurally characterized by X‐ray diffraction of single crystal along with elemental analysis.…”
Section: Introductionmentioning
confidence: 97%
“…Meanwhile, the presenting adsorbents towards MG still suffer from limited removal capacity. In addition, in order to meet the growing demand of complex dye-containing wastewater treatment, sometimes removal of all the dyes is not always necessary since some valuable chemicals in the discharge streams need to be recycled 11 12 13 14 15 36 37 38 39 40 41 .…”
mentioning
confidence: 99%
“…Recently, supramolecular hydrogels 41 , magnetic nanoparticles 19 36 and metal-organic frameworks (MOFs) 8 14 37 38 39 40 42 have generated increasing interest as dye adsorbents because of their high removal capacity, selective adsorption and separation. The selectivity is usually realized by non-covalent host–guest interactions such as π–π interaction, electrostatic interaction, hydrogen bonding, H-bonding, p–p stacking, hydrophobic interaction, and acid-base interaction between the adsorbent and dye molecules.…”
mentioning
confidence: 99%
“…According to the above results and discussion, we suppose that the reversible thermochromic behavior might be ascribed to the change of the coordination environment of Zn 2+ ions with the loss of the lattice water and terminal water molecules at different temperatures . The thermochromic or hydrochromic behaviors are based on the processes of dehydration and rehydration and the thermochromic processes are reversible for sample 1 . MOFs‐films are important for a variety of practical applications, such as the development of different functional devices .…”
Section: Resultsmentioning
confidence: 99%